2004
DOI: 10.1373/clinchem.2004.031260
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Human Chorionic Gonadotropin β-Subunit mRNA Concentrations in Maternal Serum in Aneuploid Pregnancies: A Feasibility Study

Abstract: phosphate buffer (pH 6.0) was integrated into the assay component.Fully automated immunoassay formats are available for quantification of urinary albumin in large numbers of samples. However, most of these methods are impractical or expensive. The criteria for point-of-care testing include affordable cost, a disposable device, and minimum maintenance/technical expertise required to perform tests (15 ). The sample should be applied directly to the device, which should require only a small sample volume, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 11 publications
(3 reference statements)
1
18
0
Order By: Relevance
“…Quantification of plasma placental RNA is not limited by the fetal gender or genotype, and allows marker development from disease-specific gene expression patterns. For example, our group has reported that circulating fetal RNA analysis could be applied for the noninvasive prenatal diagnosis of pre-eclampsia (PET) and fetal aneuploidies (Ng et al, 2003a;Ng et al, 2004;.…”
Section: Introductionmentioning
confidence: 99%
“…Quantification of plasma placental RNA is not limited by the fetal gender or genotype, and allows marker development from disease-specific gene expression patterns. For example, our group has reported that circulating fetal RNA analysis could be applied for the noninvasive prenatal diagnosis of pre-eclampsia (PET) and fetal aneuploidies (Ng et al, 2003a;Ng et al, 2004;.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has used the epigenetic DNA differences that exist between placenta and maternal blood cells to develop universal fetal-DNA markers (8 -10 ) that are sex-and polymorphism-independent. Furthermore, quantitative aberrations of fetus-derived mRNA transcripts have been shown in conditions such as preeclampsia (11 ) and fetal aneuploidies (12 ). The feasibility of detecting fetal chromosomal aneuploidies in maternal plasma has been demonstrated with a fetusderived PLAC4 4 (placenta-specific 4) mRNA transcript (13 ).…”
mentioning
confidence: 99%
“…Interestingly, the expression levels of placenta-specific transcripts in the plasma positively correlated with those in placental tissues (3 ), underscoring the potential clinical utility of plasma RNA analysis as a noninvasive tool to monitor placental development and fetal health. Examination of maternal circulating RNA has found clinical applications for pregnancy-or placenta-related disorders such as preeclampsia (5)(6)(7)(8), intrauterine growth retardation (9 ), and preterm birth (10 ), as well as for noninvasive testing of fetal chromosomal aneuploidies (11)(12)(13). Such developments highlight the potential utilities of RNA biomarkers for the molecular assessment of prenatal disorders.…”
mentioning
confidence: 99%